Merancang Succession Planning dan Career Planning pada Industri Kertas dan Karton - Rendy Ferdianto; Viona, Viona; Irene Vangoh; Charmaine, Charmaine; Jane Eveline (MAMEN: Jurnal Manajemen, 2023)
To achieve company goals, employees need to be encouraged in the form of rewards and opportunities to develop improvements through certain job promotions or positions according to their abilities. Succession planning at PT. Indah Kiat Pulp & Paper currently has 5 important positions namely Director, Technical Manager, Finance Manager, Marketing Manager, Production Manager and HR Manager. Because the current Director will retire, PT. Indah Kiat Pulp & Paper is looking for a replacement by selecting and assessing each of the existing Managers. To work at PT. Indah Kiat Pulp & Paper, every employee must have a value according to the criteria given by the company. There are 10 individual development programs namely job enlargement/enrichment, on the job development, special assignments, mentoring, workshops/in-class training, job rotation, action rotation, action based learning, self study, cross training and coaching/counseling. There are Engineering Managers, Finance Managers, Marketing Managers, Production Managers and HR Managers in the company's plans to make them grow by carrying out career planning with descriptions and indicators of each. The advice we can give PT. Indah Kiat Pulp & Paper should focus more on succession planning and career planning, because these two things have been proven to have a positive impact on the company.